2006
DOI: 10.1021/nl0627689
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature in Situ Large Strain Plasticity of Ceramic SiC Nanowires and Its Atomic-Scale Mechanism

Abstract: Large strain plasticity is phenomenologically defined as the ability of a material to exhibit an exceptionally large deformation rate during mechanical deformation. It is a property that is well established for metals and alloys but is rarely observed for ceramic materials especially at low temperature (∼300 K). With the reduction in dimensionality, however, unusual mechanical properties are shown by ceramic nanomaterials. In this Letter, we demonstrated unusually large strain plasticity of ceramic SiC nanowir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
194
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(207 citation statements)
references
References 34 publications
11
194
0
2
Order By: Relevance
“…This value might be slightly overestimated due to the use of a simple mechanical model. In situ TEM bending tests showed that SiC NWs could experience an elastic strain of ∼2% 232. However, the result might be affected by EBI in TEM.…”
Section: Mechanical Characterization Of Nwsmentioning
confidence: 99%
“…This value might be slightly overestimated due to the use of a simple mechanical model. In situ TEM bending tests showed that SiC NWs could experience an elastic strain of ∼2% 232. However, the result might be affected by EBI in TEM.…”
Section: Mechanical Characterization Of Nwsmentioning
confidence: 99%
“…In general, dislocations are easily generated on close-packed planes where dislocations slip with low resistance. [34][35][36][37] So we examined the dislocations on close-packed planes along several directions in the obtained TEM micrographs. Away from the zone of indentation impression, there are not so many dislocations comparing with the obvious pile-up of dislocations around grain boundaries underneath indenter impressions.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, with the reduction in dimensionality, nanostructures exhibit unique mechanical behavior, which has been demonstrated in various nanostructures. 15,16 Carbon nanotube sheets with tunable Poisson's ratio from positive to negative have been synthesized, 15 and a large strain plasticity of ceramic SiC nanowire at nearly room temperature has been directly observed in situ by a highresolution transmission electron microscopy (HRTEM) technique. 16 In this paper, we report on the unconventional growth of 1D ZnSe nanospirals via a two-stage fabrication process in which different reaction pressures are applied.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Carbon nanotube sheets with tunable Poisson's ratio from positive to negative have been synthesized, 15 and a large strain plasticity of ceramic SiC nanowire at nearly room temperature has been directly observed in situ by a highresolution transmission electron microscopy (HRTEM) technique. 16 In this paper, we report on the unconventional growth of 1D ZnSe nanospirals via a two-stage fabrication process in which different reaction pressures are applied. The morphological and structural characterizations are performed in section 3.1, which shows that ZnSe nanospirals with novel mosaic blocks compartmentalized by planar defects are obtained.…”
Section: Introductionmentioning
confidence: 99%